Virulence and pathogenicity determinants in whole genome sequence of Fusarium udum causing wilt of pigeon pea - Srivastava, Alok K.; Srivastava, Ruchi; Yadav, Jagriti; Singh, Alok K.; Tiwari, Praveen K.; Srivastava, Anchal K.; Sahu, Pramod K.; Singh, Shiv M.; Kashyap, Prem Lal (Frontiers in Microbiology, 2023)
In this study, an analysis of the first whole genome sequence of Fusarium udum, causing Fusarium wilt in pigeon pea, was carried out. The de novo assembly showed a genome size of 56.38 Mb. In this, a total of 16179 protein-coding genes were identified, out of which 11,892 (73.50 %) genes were annotated using BlastP and 8928 (55.18%) by KOG annotation. In addition, 5134 unique InterPro domains were detected. This F. udum genome was analyzed for key pathogenic genes involved in virulence, and 1060 (6.55 %) genes were identified as virulence genes as per the PHI-BASE Database. Secretome profiling indicated the presence of 1439 secretory proteins in the F. udum genome. Of those, an annotation of 506 predicted secretory proteins was carried out using the CAZyme database. Results showed that Glycosyl hydrolase (GH) family proteins were more abundant (45%) than auxiliary activity (AA) family proteins. The presence of effectors for cell wall degradation, pectin degradation, and host cell death was found. The genome comprises repetitive elements of ~ 895132 bp, 128 long terminal repeats (LTRs), and 4921 simple sequence repeats (SSRs) of 80875 bp length. Effector mining by comparison among different Fusarium species revealed five common and two specific effectors in F. udum that are related to host cell death. Furthermore, wet lab studies using PCR validated the virulent effector gene SIX (for Secreted in Xylem). Deciphering the whole genome of F. udum would be instrumental in understanding evolution, virulence determinants, host-pathogen interaction, possible control strategies, ecological behavior, and many other complexities of the pathogen.